On the Role of Psychoneuroimmunology in Oral Medicine - Lennart Seizer; Christian Schubert (International Dental Journal, 2022)
Psychoneuroimmunology (PNI) is an area of interdisciplinary research exploring the complex interactions within the immuno-neuro-endocrine system in response to psychosocial influences. Such influences can trigger neurological changes, leading to immunological effects related to the emergence and course of various diseases. This concise clinical review explores the role of PNI in oral medicine in three exemplary models of oral disease: periodontitis, herpes labialis, and oral lichen planus. Previous literature has shown that psychosocial stress is related to exacerbations in these three oral diseases and to poorer overall oral health. The presumed biological mechanisms affect the activity of stress axes, i.e. the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS), and subsequent immune system dysregulation. Although these PNI mechanisms remain poorly understood, several stress reduction interventions in clinical oral medicine have already yielded promising results. In future work, the elucidation of pathways within PNI networks will require carefully designed studies with sensitive methodology, e.g. the integrative single-case design. A biopsychosocial approach has the potential to move disease models in oral medicine from simple connections rooted in empirical dualism and reductionism to the establishment of network-based models. Further research on these complex connections should lead to novel clinical approaches and preventive strategies in oral medicine.